Whi7 is an unstable cell-cycle repressor of the Start transcriptional program - Mercè Gomar-Alba (Nature Portfolio, 2017)
The commitment of cells to a new cycle of division involves inactivation of the Start transcriptional repressor Whi5. Here the authors show that the sequence related protein Whi7 associates to G1/S gene promoters in late G1 and collaborates with Whi5 in Start repression.